1997
DOI: 10.1002/bies.950190209
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila fusome, organelle biogenesis and germ cell differentiation: If you build it…

Abstract: From stem cells to oocyte, Drosophila germ cells undergo a short, defined lineage. Molecular genetic analyses of a collection of female sterile mutations have indicated that a germ cell-specific organelle called the fusome has a central role at several steps in this lineage. The fusome grows from a prominent spherical organelle to an elongated and branched structure that connects all mitotic sisters in a germ cell syncytium. The organelle is assembled from proteins normally found in the membrane skeleton and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 44 publications
1
48
0
1
Order By: Relevance
“…Whether the fusome membranes consist of discrete ERderived vesicles or form a network of interconnected tubules has remained unresolved with evidence for both types of fusome membrane structures observed by electron microscopy (Telfer, 1975;Bü ning, 1994;Lin et al, 1994;McKearin, 1997). It is worth noting that the ER of animal cells is an ideal example of an interconnected membranous compartment and typically exists as a continuous network of branching tubules connected to the nuclear envelope.…”
Section: Ovarian Cysts Share a Common Ermentioning
confidence: 99%
See 3 more Smart Citations
“…Whether the fusome membranes consist of discrete ERderived vesicles or form a network of interconnected tubules has remained unresolved with evidence for both types of fusome membrane structures observed by electron microscopy (Telfer, 1975;Bü ning, 1994;Lin et al, 1994;McKearin, 1997). It is worth noting that the ER of animal cells is an ideal example of an interconnected membranous compartment and typically exists as a continuous network of branching tubules connected to the nuclear envelope.…”
Section: Ovarian Cysts Share a Common Ermentioning
confidence: 99%
“…Molecular genetic studies over the last ten years indicate the fusome mediates several essential steps in germline cyst development (reviewed in McKearin, 1997). The differentiation of the oocyte depends on the production of a polarized network of microtubules within the cyst, that facilitates the directional transport of specific mRNAs and proteins from the pronurse cells to the single cell that will become the oocyte (Koch and Spitzer, 1983;Theurkauf et al, 1992Theurkauf et al, , 1993.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, little is known about how ectopic expression of Bam drives GSC differentiation. In this study, we showed that knockdown of CycA significantly suppressed the GSC-loss phenotype induced by A hallmark of early germ cell development is that each round of cyst division is accompanied by a morphological change of a germ cell-specific organelle called the fusome (32). While it is observed as a spherical dot in GSCs/CBs, the fusome progressively grows upon cell division to become elongated and finally a branched structure in matured cysts.…”
Section: Discussionmentioning
confidence: 78%